Human molecular biology laboratory manual - Surzycki Stefan (Malden Blackwell, 2004)
This manual offers a hands-on, state-of-the-art introduction to modern molecular biology techniques as applied to human genome analysis. In eight unique experiments, simple step-by
Keywords: Human genetics; Laboratory manuals; Molecular biology